2023
DOI: 10.1038/s41598-023-31811-5
|View full text |Cite
|
Sign up to set email alerts
|

Loco-regional treatment with temozolomide-loaded thermogels prevents glioblastoma recurrences in orthotopic human xenograft models

Abstract: Glioblastoma multiforme (GBM) is the most aggressive primary tumor of the central nervous system and the diagnosis is often dismal. GBM pharmacological treatment is strongly limited by its intracranial location beyond the blood–brain barrier (BBB). While Temozolomide (TMZ) exhibits the best clinical performance, still less than 20% crosses the BBB, therefore requiring administration of very high doses with resulting unnecessary systemic side effects. Here, we aimed at designing new negative temperature-respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Differently, 100 µM, 200 µM, 400 µM, and 600 µM TMZ induced a dose-and time-dependent inhibition of proliferation paralleled by a progressive increase in cell death (Figure S5A,B). The three TMZ concentrations ineffective in GSCs (12.5-25-50 µM) were then tested in U87MG cells for 3, 7, and 10 days, to confirm the known drug efficacy on differentiated bulk tumor cells [60,61]. As expected, U87MG cells showed a strong sensitivity to all the concentrations of TMZ, and cell proliferation was dose-and time-dependently reduced (Figure S5C).…”
Section: Combined No Plus Temozolomide (Tmz) Treatment Further Inhibi...mentioning
confidence: 60%
“…Differently, 100 µM, 200 µM, 400 µM, and 600 µM TMZ induced a dose-and time-dependent inhibition of proliferation paralleled by a progressive increase in cell death (Figure S5A,B). The three TMZ concentrations ineffective in GSCs (12.5-25-50 µM) were then tested in U87MG cells for 3, 7, and 10 days, to confirm the known drug efficacy on differentiated bulk tumor cells [60,61]. As expected, U87MG cells showed a strong sensitivity to all the concentrations of TMZ, and cell proliferation was dose-and time-dependently reduced (Figure S5C).…”
Section: Combined No Plus Temozolomide (Tmz) Treatment Further Inhibi...mentioning
confidence: 60%
“…Compared with natural hydrogels, synthetic hydrogels are physically cross-linked by hydrogen bonding in a simple and controllable synthesis process, which has the advantages of cheap raw materials, short synthesis time, and easy operation, and under certain conditions, synthetic hydrogels can be applied as a liquid or delivered to the body. In addition, they are widely used because of their excellent biocompatibility, biodegradability, ability to carry hydrophilic and hydrophobic nanoparticles, stability, and degradability [14]. At the same time, most synthetic hydrogels are limited in their biological applications due to their low toxicity and the fact that some of the cross-linking agents are not biocompatible.…”
Section: Introductionmentioning
confidence: 99%
“…Behrooz et al demonstrated that the designed dendrimer-based pharmaceutical system was able to increase the early apoptosis from 28.2% in the case of the administration of the free drugs by up to 73.3% with the encapsulated co-delivery [ 917 ]. In orthotopic human GB xenograft models, loco-regional treatment with TMZ-loaded thermogels caused a significant reduction in the growth in tumor recurrences with no systemic toxicity, compared to untreated controls [ 918 ]. Transferrin is overexpressed in proliferating cells and cells that have undergone malignant transformation [ 919 ].…”
Section: Nanotherapiesmentioning
confidence: 99%